A geospatial data integration framework for mapping and monitoring tropical landscape diversity in Costa Rica's San Juan-La Selva Biological Corridor - Sesnie, Steven E. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho, 2006